Clinical and genetic characterization of pediatric patients with Wilson’s disease from Yunnan province where ethnic minorities gather - Wang, Yanjun; Fang, Jiahui; Li, Bin; Li, Chongyang; Liu, Shan; He, Juan; Tao, Lvyan; Li, Cuifen; Yang, Ya; Li, Li; Xiao, Shufang (Frontiers in Genetics, 2023)
Background: Wilson’s disease (WD) is an autosomal recessive disease that is caused by mutations in the ATP7B (a copper-transporting P-type ATPase) gene. The disease has a low prevalence and is characterized by a copper metabolism disorder. However, various characteristics of the disease are determined by race and geographic region. We aimed to discover novel ATP7B mutations in pediatric patients with WD from Yunnan province, where there is a high proportion of ethnic minorities. We also performed a comprehensive analysis of ATP7B mutations in the different ethnic groups found in Southwest China. Methods: We recruited 45 patients who had been clinically diagnosed with WD, from 44 unrelated families. Routine clinical examinations and laboratory evaluations were performed and details of age, gender, ethnic group and symptoms at onset were collected. Direct sequencing of the ATP7B gene was performed in 39 of the 45 patients and their families. Results: In this study, participants came from seven different ethnic groups in China: Han, Bai, Dai, Zhuang, Yi, Hui and Jingpo. Three out of ten patients from ethnic minorities presented with elevated transaminases, when compared to the majority of the Han patients. Forty distinct mutations (28 missense, six splicing, three non-sense, two frameshift and one mutation of uncertain significance) were identified in the 39 patients with WD. Four of the mutations were novel and the most frequent mutation was c.2333G > T (p.R778L, allelic frequency: 15.38%). Using the phenotype-genotype correlation analysis, patients from ethnic minorities were shown to be more likely to have homozygous mutations (p = 0.035) than Han patients. The patients who carried the c.2310C > G mutation had lower serum ceruloplasmin levels (p = 0.012). In patients with heterozygous mutations, c.3809A > G was significantly associated with ethnic minorities (p = 0.042). The frequency of a protein-truncating variant (PTV) in Han patients was 34.38% (11/32), while we did not find PTV in patients from ethnic minorities. Conclusion: This study revealed genetic defects in 39 pediatric patients with WD from Yunnan province. Four novel mutations were identified and have enriched the WD database. We characterized the genotypes and phenotypes in different minorities, which will enhance the current knowledge on the population genetics of WD in China.